Evaluation of Salt Tolerance of Moringa oleifera Lam. in Saline Paddy Soil with Added NaCl - HARUTA, Shinsuke; INADA, Yuika; KUME, Takashi; SHIMAMURA, Tetsuya (Nōgyō Nōson Kōgakkai ronbunshū, 2023)
The objective of this study is to evaluate the salt tolerance of Moringa oleifera Lam. in four different conditions of ECe (Electrical conductivity of the saturated paste extract) (Control, 4, 8, and 16 dS/m) added with NaCl to paddy soils, with the aim of utilizing Moringa oleifera Lam. as a conversion crop in salinized paddy fields. The dry matter weight of above-ground parts, excluding roots, did not differ significantly among the four conditions. The highest height and dry matter weight were observed when the plants were grown at 4 dS/m. On the other hand, dry matter weight of roots grown in 8 dS/m and 16 dS/m soils and height in 16 dS/m soil were significantly lower than those in 4 dS/m soil. The Na content per gram of dry matter increased with increasing salinity. The results indicate that Moringa oleifera Lam. grows well when the salinity is less than 4 dS/m, but growth inhibition in the roots was observed when the salinity was 8 dS/m. At 16 dS/m salinity, there was a clear growth inhibition in height, total dry matter weight, and root dry matter weight compared to other conditions.